THE RELATIONSHIP BETWEEN EXTERNAL DEBT AND EMISSIONS AND ECOLOGICAL FOOTPRINT THROUGH ECONOMIC GROWTH: TURKEY - Emrah Beşe; H. Swint Friday (Cogent Economics & Finance)
The influence of external debt on the environment is a rising issue in the rapidly developing climate crisis. This study analyzes the relationship between carbon dioxide emissions per capita, gross domestic product per capita and ecological footprint per capita by applying an autoregressive distributed lag model for the Republic of Turkey. According to the results of this study there is an inverted U relationship between carbon dioxide emissions and external debt. There is no inverted U relationship between ecological footprint per capita and external debt while there is bidirectional causal relationship between external debt and economic growth. In addition, the results reveal that economic growth has a significant impact on ecological footprint per capita in the long run. There is causal relationship from external debt to emissions. This study recommends that further analysis be done for other countries that have high foreign debt to investigate the relationship between external debt and emissions. Similar analysis may be carried out for the external debt and ecological footprint per capita nexus for future studies.